CREATIVE DRAMA, CREATIVE MINDS: CONTRIBUTIONS OF THE CREATIVE DRAMA TO THE PRESCHOOLERS’ DEVELOPMENTAL DOMAINS - Kabadayi, Abdülkadir (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
Creative drama serves as a powerful tool in the holistic development of preschoolers, offering a myriad of benefits across various domains. Its aims encompass socialization through group activities, experiential learning, and the fostering of verbal creativity. Through creative drama, preschoolers not only enhance their physical development but also express themselves verbally, refine social skills, and develop self-awareness. Moreover, creative drama plays a crucial role in shaping teachers’ perspectives toward preschoolers. In essence, creative drama provides a rich and engaging platform for preschoolers to explore, express, and learn, contributing significantly to their cognitive, emotional, and social growth during these formative years.